Puisi Digital Bertema Kesehatan Mental sebagai Sumber Pendidikan Karakter: Tinjauan Sistematis 2015–2025 - Ardhiyanti, Laila Lupita (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2025)
This study was motivated by the limited understanding of how digital poetry with mental health themes can serve as a medium for character education in the era of digital literacy. The aim of this research is to synthesize interdisciplinary findings that examine the role, effectiveness, and pedagogical implications of digital poetry in fostering students’ character and emotional well-being. A Systematic Literature Review (SLR) approach was applied by analyzing 50 qualitative, quantitative, and mixed-method studies published between 2015 and 2025. Data were collected from major academic databases such as Scopus, ERIC, and Google Scholar, then analyzed using thematic synthesis and conceptual mapping. The findings indicate that digital poetry effectively enhances emotional awareness, empathy, and psychological resilience through interactive narratives that support mental health. It also contributes to the development of character values such as responsibility, tolerance, and moral reflection through affective and technology-based pedagogical strategies. Pedagogically, integrating digital poetry requires curriculum support, teacher readiness, and equitable digital literacy. The study concludes that digital poetry represents an innovative medium for strengthening holistic character formation and developing emotional intelligence in 21st-century education. Keywords: digital poetry, mental health, character education, emotional literacy, systematic review